2013
DOI: 10.22219/jmb.v1i1.1318
|View full text |Cite
|
Sign up to set email alerts
|

Faktor -Faktor Yang Mempengaruhi Konsumen Dalam Pembelian Makanan Jajan Tradisional Di Kota Malang

Abstract: Fakultas Ekonomi Universitas Muhamadiyah MalangE-mail: uci@umm.ac.idABSTRACTThis research title is The Buying Factors Considered by Consummers On Traditional Cake inMalang City. Its aim is to learn buying factors considered by Malang residents in traditional cakes'consumption. All respondents are Malang residents who have been ever buying and consummingtraditional cake at market in Malang city. The result of research shows that there are 8 buying factorsconsidered in traditional cake consumption, namely person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
2
1
5
Order By: Relevance
“…The results of this study indicate that price affects profitability. Other studies prove that selling prices affect an increase in sales of a company's products (Ginting et al, 2014;Totanan, 2018;Yuliati, 2011). Instead, this study found that the guarantee of fried onion products as local food did not affect profitability.…”
Section: Discussioncontrasting
confidence: 52%
“…The results of this study indicate that price affects profitability. Other studies prove that selling prices affect an increase in sales of a company's products (Ginting et al, 2014;Totanan, 2018;Yuliati, 2011). Instead, this study found that the guarantee of fried onion products as local food did not affect profitability.…”
Section: Discussioncontrasting
confidence: 52%
“…Adnan (2018) menyatakan bahwa faktor budaya, sosial, dan psikologis dari konsumen, berpengaruh signifikan terhadap keputusan pembelian. Penelitian Yulianti (2011) menunjukkan bahwa faktor usia, pendidikan dan jenis pekerjaan merupakan faktor utama dalam mempertimbangkan keputusan pembelian.…”
Section: Karakteristik Konsumen Jajanan Tradisionalunclassified
“…Kabupaten Pekalongan memiliki banyak tempat wisata di berbagai kecamatan, sehingga dapat dijadikan alternatif bagi Pemerintah Kabupaten Pekalongan untuk membuka cabang Pasar Rindu Semilir agar semakin luas menjangkau masyarakat. Tempat pembelian yang menarik dan lokasi yang strategis, misalnya di pasar modern dapat memengaruhi penjualan makanan tradisional di Kota Malang (Yulianti 2011) dan di Yogyakarta (Khairullah 2020).…”
Section: Lokasi Pembelianunclassified
“…The product being sold is the same product so that the value of the product will remain the same so that it has a significant influence on purchasing decisions. Yuliati (2011) explains that the traditional taste of a product is able to drive purchasing decisions, this is because consumers want a taste that is different from other products. Isa et al (2018) explained that traditional products have an appeal to make consumers make purchases.…”
Section: Products Against Purchasing Decisionsmentioning
confidence: 99%